2019
DOI: 10.1136/bmjopen-2018-028878
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption trajectories and self-rated health: findings from the Stockholm Public Health Cohort

Abstract: ObjectiveTo investigate whether poor self-rated health and psychological distress are differentially associated with drinking trajectories over time.MethodsFrom the Stockholm Public Health Cohort, two subcohorts surveyed in 2002–2010–2014 and 2006–2010–2014 (n=23 794 and n=34 667 at baseline, respectively) were used. Alcohol consumption, self-rated health, psychological distress (measured by General Health Questionnaire-12), lifestyle factors and longstanding illness were assessed by questionnaires. Demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…Our findings echo other research which suggests that former drinkers have poorer self‐perceived general health [45] and are at higher risk of experiencing adverse outcomes including CHD and overall mortality than moderate drinkers [18, 46]. As a reason for the higher risk seen in former drinkers, the sick‐quitter hypothesis proposes that a substantial number of former drinkers have quit drinking for health reasons [47, 48].…”
Section: Discussionsupporting
confidence: 82%
“…Our findings echo other research which suggests that former drinkers have poorer self‐perceived general health [45] and are at higher risk of experiencing adverse outcomes including CHD and overall mortality than moderate drinkers [18, 46]. As a reason for the higher risk seen in former drinkers, the sick‐quitter hypothesis proposes that a substantial number of former drinkers have quit drinking for health reasons [47, 48].…”
Section: Discussionsupporting
confidence: 82%
“…The univariate regression included the crude model (model 1), whereas the multiple regression models included both the model adjusted for age and gender (model 2) and the full model that was adjusted for all the previously selected characteristics (model 3). We chose the low-risk drinking group as our reference group to align with other alcohol-related studies and because non-drinkers often experience more adverse health outcomes and, as such, are less suitable as a reference group (Rodgers et al ., 2007 ; Gémes et al ., 2019 b ). An additional analysis was performed, using a broader definition for MDD persistence defined as meeting the criteria for MDD in the prior 3-year period (instead of 12-month MDD) at the next wave.…”
Section: Methodsmentioning
confidence: 99%
“…Several epidemiological studies have demonstrated that regular tobacco use and harmful alcohol consumption are crucial determinants of cardiovascular diseases (CVDs) [ 1 , 2 , 3 ]. Although the majority of these findings come from cross-sectional analyses, increasing longitudinal evidence has shown that persistent patterns of tobacco and alcohol consumption influence CVDs [ 4 , 5 , 6 ]. The association between smoking patterns and chronic diseases and all-cause mortality is well documented [ 7 ], and longitudinal research has shown the health benefits of smoking cessation, particularly if it occurs early in life [ 8 ].…”
Section: Introductionmentioning
confidence: 99%